Las abogadas y los abogados: modernas, modernos y coloniales - Bazán Seminario, César (2019)
Following the lines of decolonial thought, I suggest that lawyers reproduce patterns of the matrix of colonial power through their actions. In the first part of this article I describe what the decolonial option is, while in the second part I analyze lawyers and law schools paying close attention to the signs of coloniality/modernity within them. As a result, I identify lawyers as the legal guardinas of colonial power and law schools as places that reproduce the logic of modernity/coloniality.